ANALISA KEPUASAN PELANGGAN UNTUK MENINGKATKAN PELAYANAN DI UNIVERSITAS BUNDA MULIA - Rudy Santosa Sudirga (Universitas Bunda Mulia, 2017)
The purpose of the research is to integrate relevant literature theory and develop a comprehensive research model of service quality to procure customer satisfaction. In this research, we present a holistic systems approach that utilizes total quality management decision in a seamless fashion to improve satisfaction and perception related to the service provided by Universitas Bunda Mulia to the students, students parents, other universities movement students, and other students. At the same time, other university departments’ important objectives, such as the implementation of an ongoing in-house procedure that supports its continuous improvement program, are taken into account. In this research, results that document the improved service quality system performance to procure customer satisfaction are further tested for their reliability and validity. Therefore, the result will be the proper and true relationship between customer satisfaction and perceived service quality that could be used either for Universitas Bunda Mulia or other universities and eduction institutions. Conceptual and managerial implications of the findings should be further discussed by Universitas Bunda Mulia to procure and achieve a much better performance in the next coming years.Key Words- Customer, Satisfaction, and Quality